Analisis Rendahnya Minat Membaca Di Kalangan Siswa Dan Strategi Peningkatannya - Muhamad Yusuf Tujiri; Saifun Nasri; muhammad ijanur wahid (Universitas Islam Raden Rahmat Malang, 2026)
Reading interest among Indonesian students remains relatively low and constitutes a serious problem in education. This study aims to identify the problem of low reading interest, analyze the challenges faced, and formulate effective solutions to increase student interest in reading. The method used was a literature review, analyzing various references related to student reading interest. The results indicate that low reading interest is caused by various factors, such as the influence of digital technology, a lack of early reading habits, limited access to quality reading materials, and unengaging learning methods. Solutions offered include developing digital literacy, strengthening the role of families and schools, literacy-based learning innovations, and utilizing technology as a literacy medium. Keywords: reading interest, students, literacy, education, reading culture